Strutture tridimensionali nei manuali di Chimica di fine Ottocento e inizio Novecento - Chioccioli, Matteo (Chimica nella Scuola, 2025)
Graphical representations of three-dimensional structures play a pivotal role in the field of chemistry education. Their correct interpretation is indeed essential for a full understanding of basic concepts that are central for both organic and inorganic chemistry. Students should have a deep knowledge of the correct meaning of the symbolic representations that appear in school and university manuals in order to avoid misunderstandings and a meaningless learning of the discipline. The aim of the present work is to analyse two important historical examples: the three-dimensional representations of tetrahedral carbon, proposed by van’t Hoff and Le Bel in 1874 to describe the physical isomerism of organic compounds, and the geometry of metal complexes introduced by Werner in 1893. This work investigates the way in which these three-dimensional representations were received and presented in school and university textbooks published in the late nineteenth and early twentieth centuries, before the introduction of techniques of structural investigation such as X-ray crystallography.